Shad fishing on the Tar River, 1963. - (:unkn) unknown (Forsyth County Public Library)
WSJ 4-21-63 p.B5.
Shad fishing on the Tar River, 1963.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth